Meningkatkan Kemandirian Anak melalui Rutinitas Harian di Lingkungan Sekolah Dasar - Nazwa May A; Ibnu Muthi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to systematically examine how daily routines in elementary school environments play a role in increasing children's independence. Independence is an important skill that needs to be developed early on, including personal responsibility, initiative, and self-discipline. The methodology used in this study is a literature study with a qualitative descriptive approach, in which the author synthesizes various journals, books, and relevant previous research results. The results of the study indicate that various forms of daily routines such as class duty, guarding personal belongings, morning prayers, and managing break times play a significant role in forming independent behavior in children. The mechanisms that occur in this process include habituation, repetition, consistency, and positive reinforcement that encourages the internalization of independence values. In addition, the role of teachers as facilitators, models, and feedback providers has proven to be a key factor in success, accompanied by the support of an orderly and structured school environment. The conclusion of this study confirms that daily routines are not just technical activities, but are an effective medium in character education that has a direct impact on the formation of children's independence. Collaboration between schools and families is an important aspect in optimizing the results of this habituation.